Corporate governance mechanisms, institutional ownership and yield spreads of conventional bonds and sukuk / Noriza Mohd Saad - Mohd Saad, Noriza (Institute of Graduate Studies, UiTM, 2018)
Sukuk yields mimic those of conventional bonds due to having similar features. This motivated the study. Sukuk are shariah-compliant securities that offer different structures to those of conventional bonds. Therefore, it is believed that the spreading of yields should also be different. Agency theory explains the relationship between principal and agent and the possible misalignment of interest of both parties is reflected through what is termed agency cost. Reducing this agency cost requires monitoring and controlling in public listed firms which are represented by institutional investors which delegate this responsibility to the appointed board of directors (BOD). The presence of key institutional investors/owners and certain BOD characteristics as highlighted by the Malaysian Code on Corporate Governance (MCCG) may influence the yield to maturity (YTM) of conventional bonds and sukuk. It is argued that higher institutional ownerships will produce enhanced active monitoring on the cost of debt and presumably more control on the likelihood of default risk as measured by the yield spreads for conventional bonds and sukuk. Thus, the main objective of this study is twofold. First, to investigate the significant mean difference between conventional bonds and sukuk’ yield spreads. Second, to investigate the relationship between these two yield spreads instruments with corporate governance mechanisms. The data is obtained from firm issuers’ annual reports, the Bond info Hub of the Malaysian Central Bank, the Rating Agency Malaysia (RAM), the -alaysian Department of Statistics and Bloomberg databases for the period beginning 2000 to 2014 for 256 and 405 tranches of long-term and medium-term issurances of conventional bonds and sukuk respectively…